Spin-polarized confined states in Ag films on Fe(1 1 0). (16th November 2017) - Moras, P; Bihlmayer, G; Vescovo, E; Sheverdyaeva, P M; Papagno, M; Ferrari, L; Carbone, C
Abstract: Spin- and angle-resolved photoemission spectroscopy of thin Ag(1 1 1) films on ferromagnetic Fe(1 1 0) shows a series of spin-polarized peaks. These features derive from Ag sp -bands, which form quantum well states and resonances due to confinement by a spin-dependent interface potential barrier. The spin-up states are broader and located at higher binding energy than the corresponding spin-down states at Γ ̄, although the differences attenuate near the Fermi level. The spin-down states display multiple gap openings, which interrupt their parabolic-like dispersion. First-principles calculations attribute these findings to the symmetry- and spin-selective hybridization of the Ag states with the exchange-split bands of the substrate.